Identification and treatment of intestinal malrotation with midgut volvulus in childhood: a multicenter retrospective study - Yang, Xiaofeng; Wang, Wei; Wang, Kun; Zhao, Jingquan; Sun, Liandong; Jiang, Shuai; Wang, Yewen; Feng, Wenyu; Ding, Guojian; Fu, Tingliang; Li, Aiwu; Geng, Lei (Frontiers in Pediatrics, 2024)
Background: Intestinal malrotation is uncommon and delayed diagnosis may have fatal consequences. The aim of this study was to investigate the identification and treatment of malrotation in children.Clinical data, imaging, operative findings, and early postoperative outcomes of 75 children with malrotation were retrospectively analyzed.The mean age was 6.18 ± 4.93 days and 51.26 ± 70.13 months in the neonatal group (56 cases) and non-neonatal group (19 cases). Sixty-seven patients were under 1 year of age at the time of diagnosis. The occurrence of bilious vomiting and jaundice was significantly higher in the neonatal group (89.29%) than in the non-neonatal group (37.5%), p <0.05 and <0.01, respectively. The incidence of abnormal ultrasound findings was 97.30% and 100%, respectively, and the sensitivities of the upper gastrointestinal series were 84.21% and 87.5%, respectively. Sixty-six (88%) patients had midgut volvulus, including in utero volvulus (two cases) and irreversible intestinal ischemia (four cases). Most neonates (89.29%) underwent open Ladd's procedure with a shorter operative time (p < 0.01). Reoperation was performed for postoperative complications (four cases) or missed comorbidities (two cases).Conclusions: Non-bilious vomiting was the initial symptom in >10% of neonates and nearly 40% of non-neonatal cases. Emergency physicians and surgeons should be cautious about ruling out malrotation in patients with non-bilious vomiting. Ultrasound can obviate the need for contrast examinations owing to its higher diagnostic accuracy and rapid diagnosis and can be recommended as a first-line imaging technique. Open surgery is still an option for neonatal patients.